Stroke Prevention with Lifestyle Modification: A Literature Review - Syafrizal, Raina Alexandriana Putri; Ardian, Laurentius Johan; Seto, Andreas Aryo Bayu (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Background : Stroke is one of the common caused of death in the world. Lifestyle modification is to prevent the stroke occurred and to reduce the risk of new stroke events. Method: method used is a literature review through international journals. Discussion : This literature review shows that there is a poor correlation between increased knowledge about stroke and changes in lifestyle behavior. Modification of risk factors is very important for primary and secondary stroke prevention. Long-term lifestyle modification is difficult to maintain and require comprehensive and individualized intervention. Increasing the understanding of stroke risk will prevent a signiﬁcant number of strokes before they lead to death and disability. In this way, two major strategies could be applied: the high-risk strategy and the mass (population-based)strategy. The high-risk one deals with individuals with a higher risk of developing stroke and includes lifestyle changes (i.e., reduced salt and alcohol intake, physical activity, weight loss, smoking cessation, etc.) and pharmacological interventions (i.e BP and lipid lowering agents, antiplatelet medications, etc.). Conclusion: Lifestyle modifications should address not single but multiple cardiovascular risk factors to effectively reduce the risk of stroke. Lifestyle modifications on a personal level should include adequate physical activity, a healthy diet, the cessation of smoking and alcohol consumption, and stress reduction. Physical activities should be performed in a healthy environment without air pollution.